Representasi Perjuangan Perempuan dalam Novel Wedding Agreement Karya Mia Chuz - Widianti, Nurhannah; Rivaldi, Sacandra Aji; Labibah, Shopa; Solihin, Nia (MUWAZAH: Jurnal Kajian Gender, 2020)
This article analyzes the novel Wedding Agremeent which tells the struggle of a woman named Tari in defending her household. Although he did not obtain birth, mental and cheating rights, he still carried out his responsibilities as a wife. The purpose of the analysis, which is to describe the religious values ​​implemented by Tari in dealing with domestic conflicts. This study also illustrates the forms of his struggle in rejecting contract marriages. The methodology used is descriptive qualitative approach to criticism of feminism. The results of the analysis show that the Islamic values ​​that appear in the person of Dance, which is always closer to God, patient, independent, obedient to the husband, and polite. Meanwhile, the form of struggle carried out by Tari as a wife, among others (1) did not rashly make decisions by asking advice from the closest people; (2) always looking for ways to maintain the household; (3) trying to use the time to be a good wife by meeting the various needs of her husband.